PENGEMBANGAN E-BOOK MATEMATIKA INTERAKTIF BERBASIS KONTEKSTUAL UNTUK SISWA SMP KELAS VIII - Husnul Khatimah; Fatmah Fatmah; Suciyati Suciyati (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
The purpose of this research is to describe the process and results of the development of a contextual-based interactive mathematics e-book for Grade VIII students of junior high school. This type of research is development research adopting the ADDIE development model which consists of 5 phases namely analysis, design, development, implementation and evaluation. The Analysis phase is related to conducting a needs analysis, namely an analysis of student needs and an analysis of teacher needs. The Design phase is the phase of making design specifications according to the needs analysis, in this phase the researcher makes flowcharts and storyboards. Development phase is the process of realizing the design into a product. In the Implementation or implementation phase, researchers conduct small-scale trials in the implementation phase. Then in the Evaluation phase, the researcher evaluates the implementation of the four stages in the ADDIE research model. The test subjects in this study were material experts, media experts, practitioners, and practicality tests (users). Based on the validation results of material experts that the percentage of validity is 79.69% with a high category, media experts with a percentage of 81, 94% are very high categories, and the results of practitioner validation are very high with a percentage of 90.18%. Then the practicality test with a percentage of 90.54% shows that the level of practicality of the e-book is very high. From the results obtained, it can be concluded that an interactive mathematics e-book based on contextual material on a system of two-variable linear equations (SPLDV) for Grade VIII junior high school students is valid and practical to apply to the learning process in class and outside the classroom independently.